EFEKTIVITAS PROGRAM BUMDES TUNAS HARAPAN JAYA DESA PUO RAYA KECAMATAN TANDUN KABUPATEN ROKAN HULU TAHUN 2020 - Sitorus, Sonta Ulina; Yusri, Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
ABSTACT BUMDes is defined as a business entity whose capital is all or most of it is held by the village based on the wealth and resources available in the village. BUMDes Tunas Harapan Jaya is one of the BUMDes held to help the community's economy. The regulation underlying the procurement of BUMDes is PP 11 of 2021 concerning Village-Owned Enterprises. In its implementation, there are obstacles in achieving program objectives and program monitoring. The purpose of this study is to determine and explain the effectiveness of the implementation of the BUMDes Tunas Harapan Jaya program in 2020. The purpose of this study is to determine and explain the effectiveness of the implementation of the BUMDes Tunas Harapan Jaya program in 2020. The research location is at BUMDes Tunas Harapan Jaya located in Puo Raya Village, Tandun District, Rokan Hulu Regency. This study uses a qualitative research type with a descriptive approach and in data collection the researcher uses interview and documentation techniques. Data analysis techniques through the stages of data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that there are BUMDes Tunas Harapan Jaya programs in Puo Raya Village, Rokan Hulu Regency in 2020 that are effective and ineffective. The programs that are effective are the savings and loan program and the building store program. Ineffective programs are the farmer's saprotan unit program, the BRILink program and the chicken coop program. BUMDes Tunas Harapan Jaya is expected to improve the quality and quantity of performance in order to carry out effective program activities in accordance with previously set goals. Keywords: Effectiveness, Program, BUMDes